DEGENERATIVE SYSTEM OF POPULAR SOVEREIGNTY BY POLITICAL PARTIES THROUGH THE INSTRUMENT OF THE RECALL RIGHTS - Malicia Evendia; Ade Arif Firmansyah (PRANATA HUKUM, 2025)
The existence of the term "party officials" which is increasingly blatant, seems to normalize the power of political parties by party leaders who are subjectively able to subordinate their members who are in government. Several cases indicate a shift in popular sovereignty towards political party sovereignty through the instrument of recall rights. This becomes a problem regarding the position and portion of people's votes in general elections which can be negated by political parties. This research uses doctrinal research methods as well as legal and conceptual approaches. The results of the study show that: first, the existence of the instrument of political party recall rights can be degenerative to the essence of popular sovereignty that has been running through the general election mechanism, this is because the existence of political party recall rights causes a shift in popular sovereignty to political party sovereignty. Second, the constitutionalization of the dismissal of legislative members is an effort of preventive legal protection in maintaining popular sovereignty based on the constitution (constitutional democracy). Therefore, it is necessary to increase a high level of commitment in providing certainty of provisions for the dismissal of legislative members in the constitution.